Anomalies of the branchial arch apparatus in children: case series and review of literature - Jain, Neha; Dham, Ruchima; Shishodia, Shama; Mahajan, Nidhi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Branchial apparatus develop between the 3rd and 7th weeks of embryonic life. There are five mesodermal arches separated by invaginations of ectoderm and endoderm. Branchial anomalies are result of aberrant embryonic development and are rarely seen in clinical practice. The objective of this article is to present few cases of branchial arch anomalies and to discuss the clinical presentation, diagnosis and surgical approach of such lesions in pediatric age group.